Effects of Shiga Toxin 2 on Lethality, Fetuses, Delivery, and Puerperal Behavior in Pregnant Mice - Yoshimura, Kazuaki (American Society for Microbiology, 2000)
Shiga toxin 2 (Stx2) is produced by enterohemorrhagic Escherichia coli (EHEC) and is known as the major virulence factor of EHEC. The aim of this study was to evaluate the effects of Stx2 on (i) maternal lethality, (ii) fetuses, (iii) delivery period, and (iv) maternal behavior after delivery. Timed pregnant ICR mice were injected intravenously with Stx2 on day 5 of pregnancy (early stage) or on day 15 (late stage). In early-stage experiments, the number of normal fetuses of mice injected with Stx2 was significantly lower than that of control mice. In late-stage experiments, mothers injected with Stx2 delivered normal numbers of neonates, but could not take care of them. The lethal doses of Stx2 were not different for pregnant and nonpregnant female mice at either stage. We conclude that Stx2 is toxic to the fetus in early pregnancy and affects maternal puerperal behavior in late pregnancy.